Fasti ecclesiae hibernicae: the succession of the prelates and members of the cathedral bodies in Ireland - Cotton, Henry (Hodges and Smith, 1851-60., 1851)
v. 1. The Province of Munster.--v. 2. The Province of Leinster.--v. 3. The Province of Ulster.--v. 4. The Province of Connaught.--v. 5. Illustrations, corrections and additions to which are added indexes to the whole work.